Failover Performance Analysis on Redundancy Link using Gateway Load Balancing Protocol - Trisari Dewi Noviyanti Bertha Mira; Fajar Hariadi (Politeknik Ganesha Medan, 2023)
Universitas Kristen Wira Wacana carries out various activities using an internet connection. Realizing the importance of this internet connection, the campus provides two different sources of internet connection. The first internet source (ISP1) has a speed of 100 Mbps, while the second internet source (ISP2) has a speed of 20 Mbps. The configuration that is currently used is less than optimal because if one of the internet sources used is disconnected, the internet connection for some campuses will be cut off, causing activities to be disrupted. In addition, the distribution of network loads is still not optimal where the second internet source (ISP2) is not used optimally due to the lack of activities that use this internet source. To overcome these two problems, a design was made by implementing the Gateway Load Balancing Protocol (GLBP) which can act as a redundancy link as well as load balancing. The simulation results of the implementation of GLBP can continue to provide internet connections to all local networks even though one internet line is disconnected and is able to divide the network load with a weight scale of 5 to 1, 5 weights for 100 Mbps internet connections and 1 weight for 20 Mbps internet connections. The failover and recovery process can be done in 1.36 seconds and 1.57 seconds if the path that is interrupted is the path to the internet, while if the path that is disconnected is the path to the local network, the failover and recovery process takes 7.70 seconds and 8.15 seconds, respectively.